An experimental study on vortex-generator insert with different arrangements of delta-winglets. (15th March 2015) - Khoshvaght-Aliabadi, M.; Sartipzadeh, O.; Alizadeh, A.
Abstract: Heat transfer enhancement in a tube using the VG (vortex-generator) insert with different arrangements of the delta-winglets is investigated. Fourteen VG inserts with the longitudinal and forward arrangement of the delta-winglets are made from the aluminum sheets with a length of 350 mm, a width of 14.5 mm, and a thickness of 0.6 mm. The heat transfer and pressure drop results achieved from the use of the VG inserts inside the tube are compared with those obtained for the plain tube. It is found that at the transitional flow through the plain tube, Notter-Rouse equation predicts the current experimental Nusselt number better than Gnielinski equation. Also, the experimental results reveal that the use of the VG inserts inside the tube yields higher heat transfer coefficient and pressure drop than the plain tube, and these parameters augment with increasing the delta-winglets. The appropriate tradeoff between the enhanced heat transfer and the friction is found by using a special arrangement of the delta-winglets on the VG insert which presents the highest heat transfer coefficient as well as the maximum values of considered PEC (performance evaluation criterion). The maximum PEC of 1.41 is found for this VG insert at Re = 8715. Highlights: Effect of different arrangements of delta-winglets on VG insert is investigated. Experiments are performed in transitional flow regime (3485 < Re < 8715). Two side cut with four delta-winglets on VG insert shows higher values of PEC. The maximum PEC of 1.41 is obtained at Re = 8715.